Moving Shakespeare Indoors : Performance and Repertoire in the Jacobean Playhouse - Gurr, Andrew; Karim-Cooper, Farah (Cambridge : Cambridge University Press, 2014)
Shakespeare's company, the King's Men, played at the Globe, and also in an indoor theatre, the Blackfriars. The year 2014 witnessed the opening of the Sam Wanamaker Playhouse, based on seventeenth-century designs of an indoor London theatre and built within the precincts of the current Globe on Bankside. This volume, edited by Andrew Gurr and Farah Karim-Cooper, asks what prompted the move to indoor theatres, and considers the effects that more intimate staging, lighting and music had on performance and repertory. It discusses what knowledge is required when attempting to build an archetype of such a theatre, and looks at the effects of the theatre on audience behaviour and reception. Exploring the ways in which indoor theatre shaped the writing of Shakespeare and his contemporaries in the late Jacobean and early Caroline periods, this book will find a substantial readership among scholars of Shakespeare and Jacobean theatre history.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Blackfriars Theatre (London, England)